Socijalni rad / Social Work: Pojam, predmet, teorija i praksa / Notion, Subject, Theory and Practice - Šerić, Nedreta (Pregled: časopis za društvena pitanja / Periodical for social issues, 2017)
In this paper, the author analyzes certain social work definitions in the context of theory and practice. She points to the problems and difficulties in defining social work, discussing the possibilities of establishing social work science, and challenges that definitions face in in the 21st century. In particular, she elaborates attitudes about the important factors of social work science subjects, social work research subjects and subjects of practice, or social work practice. She also gives significant attention to the influence of social factors on the construction and the way of shaping the theory and social work practice. In the end, she examines the relationship and link between theory and practice, theory and research in social work, and the connection of research into social work and practice.